The 5th World Congress on Agroforestry July 17-20, 2022, in Québec City, Canada - Trébuchon, JF (BOIS & FORETS DES TROPIQUES, 2022)
On July 17-20, 2022, in Québec City, Canada, will be held the Fifth World Congress on Agroforestry: Transitioning to a Viable World. This congress will be an opportunity to stimulate an open and inclusive dialogue between various stakeholders from around the world including farmers, researchers, advisors, policy makers, and representatives from the government, the civil society and the private sector. Considering agroforestry participates in enhancing soil health, protecting water quality, increasing biodiversity, mitigating and adapting to climate change, and providing food security, health and revenues, it is an essential component of the needed ecological, energetic, social and economic transition. This critical transition can and must be achieved through a participatory collaboration process that helps building bridges between research, policy decisions and field work. The Fifth World Congress on Agroforestry will help creating or strengthening those connections by promoting knowledge sharing for a transition to a unified and healthy world.